Does a familial subtype of complex regional pain syndrome exist? Results of a systematic review. Issue 1 (1st January 2019) - Modarresi, S.; Aref-Eshghi, E.; Walton, D. M.; MacDermid, J. C.
ABSTRACT: Background and Objective: Complex regional pain syndrome (CRPS) is a chronic condition characterized by severe regional pain, allodynia, hyperalgesia, and functional impairment. The aim of this systematic review is to investigate whether a familial subtype of CRPS (fCRPS) exists and to determine whether people with fCRPS have specific characteristics. Methods: Databases CINAHL, Medline, PsycINFO, and PubMed were searched with no date limitation. Quality of reporting was assessed using the Scottish Intercollegiate Guidelines Network scale and the Joanna Briggs Institute's checklists. Results: Eight studies were included. Family relationships were defined as any immediate (i.e., parents or siblings) or blood relatives. A combination of participants with known or unknown causes for CRPS was recruited. The studies in this review support the potential for the existence of fCRPS, although this included less than 25% of those affected. People with potential fCRPS showed more severe symptoms, more sites involved, a higher percentage of spontaneous onset, and earlier age at onset. An elevated sibling recurrence risk ratio of 5.6 (95% confidence interval [CI], 3.0 to 9.8) was reported for people under 50. None of the studies established a pattern of heritability. Therefore, the most likely explanation for heritability would be a multifactorial model in which cumulative and interactive Gene × Environment effects may be involved. Conclusions: This systematic review supports the potential for the existence of fCRPS; however, all identified studies used uncontrolled case reports, case series, and case–control designs that cannot provide evidence of causation. Further studies are required to reveal the heritability and genetic structure of fCRPS.